PENGARUH PERILAKU KARYAWAN DAN KEPUASAN KERJA TERHADAP PRODUKTIVITAS SUMBER DAYA MANUSIA SEKRETARIAT DPRD - Lamidi, Muhamad Ghufron & (Universitas Slamet Riyadi, 2009)
ABSTRACT This research is conducted to know the significancy between : (1) the officer behavior to the officer productvity, (2) the work satisfy to the officer productvity. The population is the officer at secretariat DPRD districk of Sukoharjo 2008 as many as 33 persons and the sample are 33 person. the technique of gathering the data is using inquiry sheet through validity test and reliability test. The analysis technique uses simple regression with classical assumption uses SPSS program version 12. The analysis results are : (1) the inquiry of the officer behavior variable is valid, the inquiry of work satisfy variable is valid. the variabilityâ€™s result is reliable, (2) the multicolinierity test shows there is multicolinierity so one of variable must be deleted on test; heteroskedasticity test shows the free variable does not of affect to the residue; the autocorrelation test shows that there is no autocorrelation and normality test shows that the residue distribution is normal. The conclusion of the research: (1) hypothesis which says: â€œassumpted there is a significant influence between the work satisfy to the officer productivity at Sekretariat DPRD District of Sukoharjoâ€ is true, (2) hypothesis which says